Can reflective teaching promote resilience among Iranian EFL teachers? A mixed-method design. Issue 3 (4th May 2021) - Ayoobiyan, Hakimeh; Rashidi, Nasser
ABSTRACT: Teacher resilience as a capacity for teachers enables them to bounce back and thrive rather than just survive in challenging circumstances. Although reflection is theoretically introduced to enhance resilience, there is little empirical evidence to support the relationship. To fill the gap, this study investigates the association between Iranian EFL teachers' reflective practice and their resilience. To this end, seventy-five EFL teachers completed the English language teaching reﬂection inventory and the resilience scale. The results indicated the positive effect of different subscales of teachers' reflection on their resilience. The findings of correlational analysis demonstrated that all five reflection subscales had a significant positive relationship with teachers' resilience. Besides, the results of multiple regression analysis also showed that two subscales of cognitive reflection and metacognitive reflection were good predictors of teacher resilience. In the qualitative phase, the contribution of different subscales of reflection in promoting resilience was examined. Based on these findings, suggestions for further research were presented and pedagogical implications were proposed.